Autism Spectrum Disorders: Developmental Trajectories, Neurobiological Basis, Treatment Update - Yuri Bozzi (Frontiers Research Topics, 2017)
This Research Topic has the aim to fill the gap of the many unresolved scientific issues on Autism Spectrum Disorders (ASD) that are still in need of investigation, Targeted treatments based on the understanding of the underlying pathogenic mechanisms of disease are still lacking. Further research is awaited and should be obtained through a significant effort on experimental treatment trials and neuroscience research. This Topic is divided in two main sections, one covering clinical issues and another on basic neurosciences of Autism Spectrum Disorders. A more detailed description of the contents of the articles is provided in the editorial at the beginning of the issue.